Assessing Defragmentation Strategies for FPGAs - Gericota, Manuel G. (2017)
Fragmentation on dynamically reconfigurable FPGAs is currently a major obstacle to the efficient management of its logic space. When resource allocation decisions have to be made at run-time a relocation of currently running functions may be necessary to release enough contiguous resources to implement incoming functions. Relocation should have into account any specifics of function’s functionality and also those of the FPGA’s architecture as to not affect system’s performance. A simple and fast method to assess performance degradation of a function during relocation is proposed in this paper. This method is based on previous function labelling and on the new concept of proximity vectors.